PENGARUH PENERAPAN MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA - Sumita, Isma; Berliani, Teti (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2024)
This study aims to determine the effect of the application of classroom management on the learning motivation of class VIII students at SMP Negeri 1 Kapuas Barat Kapuas Regency. The research method used was a quantitative approach, with the research subject being class VIII students of SMP Negeri 1 Kapuas Barat Kapuas Regency in the 2023⁄2024 academic year totaling 76 students. The data in the study were collected using a questionnaire technique, then analyzed using a simple linear regression formula. The results showed that the simple linear regression equation of Y = a + bX was Y = 16.693 + 0.700X. The constant value (a) is 16.693. Based on the results of hypothesis testing, t count 8.329> t table 1.992 was obtained, so that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This shows that the classroom management variable has a significant effect on student learning motivation at State Junior High School 1 Kapuas Barat Kapuas Regency by 48.4% and the rest is influenced by other variables not examined.